Pengaruh Umur Induk Terhadap Daya Tunas Dan Daya Tetas Telur Ayam Strain Lohman - Ginanjar Prasetyo; Soegeng Herijanto; Fani Evadewi; Tri Sukmaningsih (Fakultas Peternakan. Unwiku, Purwokerto, 2025)
This research aims to determine the effect of parental age on fertility and hatchability of Lohman strain chicken eggs. This research uses quantitative methods, collecting data using observation, documentation and interview techniques. The data obtained were then analyzed using RAL variance analysis with a unidirectional pattern with 3 treatments, namely P1 (mother's age 27 weeks), P2 (mother's age 37 weeks), P3 (mother's age 47 weeks), which was repeated in 6 repetitions. Variables seen from the values of fertility and hatchability. The results of the analysis of variance stated that the age of the parent had an effect (P<0,01) on the fertility and hatchability of Lohman strain chicken eggs